CFD investigation of iodine mass transfer in venturi scrubbing solution of Filtered Containment Venting System. (March 2019) - Ashfaq, Talha; Qureshi, Kamran; Shah, Ajmal; Waheed, Khalid; Siddique, Waseem; Irfan, Naseem; Ahmed, Masroor; Farooq, Amjad
Abstract: Removal of elemental iodine from gases using Filtered Containment Venting System (FCVS) was studied. Iodine was scrubbed from gases by passing it through venturi placed in scrubbing solution. This task was performed using ANSYS 14.0 FLUENT. Scrubbing solution was aqueous solution of sodium hydroxide and sodium thiosulphate in water. Two phase Euler-Euler multiphase model was used while transfer of iodine from gaseous phase to liquid phase was modelled using species transport model. No specific model was available in any CFD software package to model mass transfer of iodine in scrubbing solution. Therefore, a user defined function (UDF) for iodine mass transfer based on mathematical model proposed by Majid et al. was developed and implemented through FLUENT. Droplet diameter effect on mass transfer of iodine was studied. Large decrease in gas phase iodine, large mass transfer rate and sharp increase in liquid phase iodine was observed on decreasing droplet diameter. About 98% removal efficiency was observed in case of 1 micron droplet diameter while it decreased as the droplet diameter was increased. Thus, validating the mass transfer model for removal of iodine as removal efficiency lies within range reported in previously published experimental results. Increase in liquid volume fraction along venturi length was also noted due to mass transfer of iodine. Liquid droplets of smaller diameter achieved peak velocity close to gas phase. This peak velocity shifted more towards the diverging section as droplet diameter was increased.